Graphitic carbon nitride prepared from urea as a photocatalyst for visible-light carbon dioxide reduction with the aid of a mononuclear ruthenium(II) complex - Maeda, Kazuhiko; An, Daehyeon; Kuriki, Ryo; Lu, Daling; Ishitani, Osamu (Beilstein Journal of Organic Chemistry, 2018)
Graphitic carbon nitride (g-C3N4) was synthesized by heating urea at different temperatures (773–923 K) in air, and was examined as a photocatalyst for CO2 reduction. With increasing synthesis temperature, the conversion of urea into g-C3N4 was facilitated, as confirmed by X-ray diffraction, FTIR spectroscopy and elemental analysis. The as-synthesized g-C3N4 samples, further modified with Ag nanoparticles, were capable of reducing CO2 into formate under visible light (λ > 400 nm) in the presence of triethanolamine as an electron donor, with the aid of a molecular Ru(II) cocatalyst (RuP). The CO2 reduction activity was improved by increasing the synthesis temperature of g-C3N4, with the maximum activity obtained at 873–923 K. This trend was also consistent with that observed in photocatalytic H2 evolution using Pt-loaded g-C3N4. The photocatalytic activities of RuP/g-C3N4 for CO2 reduction and H2 evolution were thus shown to be strongly associated with the generation of the crystallized g-C3N4 phase.
Keywords: artificial photosynthesis; heterogeneous photocatalysis; hybrid material; metal complexes; solar fuels

(untitled) - Liebig, J. (Ann. Pharm. (Lemgo, Ger.), 1834)

(untitled) - Wang, Y.; Wang, X.; Antonietti, M. (Angew. Chem., Int. Ed., 2012)

(untitled) - Zheng, Y.; Lin, L.; Wang, B.; Wang, X. (Angew. Chem., Int. Ed., 2015)

(untitled) - Zhang, J.; Chen, Y.; Wang, X. (Energy Environ. Sci., 2015)

(untitled) - Kuriki, R.; Maeda, K. (Phys. Chem. Chem. Phys., 2017)

(untitled) - Yin, S.; Han, J.; Zhou, T.; Xu, R. (Catal. Sci. Technol., 2015)

(untitled) - Fang, Y.; Wang, X. (Chem. Commun., 2018)

(untitled) - Maeda, K.; Sekizawa, K.; Ishitani, O. (Chem. Commun., 2013)

(untitled) - Maeda, K.; Kuriki, R.; Zhang, X.; Wang, X.; Ishitani, O. (J. Mater. Chem. A, 2014)

(untitled) - Kuriki, R.; Sekizawa, K.; Ishitani, O.; Maeda, K. (Angew. Chem., Int. Ed., 2015)

(untitled) - Kuriki, R.; Ishitani, O.; Maeda, K. (ACS Appl. Mater. Interfaces, 2016)

(untitled) - Maeda, K.; Kuriki, R.; Ishitani, O. (Chem. Lett., 2016)

(untitled) - Kuriki, R.; Matsunaga, H.; Nakashima, T.; Wada, K.; Yamakata, A.; Ishitani, O.; Maeda, K. (J. Am. Chem. Soc., 2016)

(untitled) - Kuriki, R.; Yamamoto, M.; Higuchi, K.; Yamamoto, Y.; Akatsuka, M.; Lu, D.; Yagi, S.; Yoshida, T.; Ishitani, O.; Maeda, K. (Angew. Chem., Int. Ed., 2017)

(untitled) - Wada, K.; Eguchi, M.; Ishitani, O.; Maeda, K. (ChemSusChem, 2017)

(untitled) - Wada, K.; Ranasinghe, C. S. K.; Kuriki, R.; Yamakata, A.; Ishitani, O.; Maeda, K. (ACS Appl. Mater. Interfaces, 2017)

(untitled) - Lin, J.; Pan, Z.; Wang, X. (ACS Sustainable Chem. Eng., 2014)

(untitled) - Wang, S.; Lin, J.; Wang, X. (Phys. Chem. Chem. Phys., 2014)

(untitled) - Walsh, J. J.; Jiang, C.; Tang, J.; Cowan, A. J. (Phys. Chem. Chem. Phys., 2016)

(untitled) - Zhao, G.; Pang, H.; Liu, G.; Li, P.; Liu, H.; Zhang, H.; Shi, L.; Ye, J. (Appl. Catal., B: Environ., 2017)

(untitled) - Maeda, K. (J. Photochem. Photobiol., C, 2011)

(untitled) - Maeda, K.; Domen, K. (Bull. Chem. Soc. Jpn., 2016)

(untitled) - Goettmann, F.; Fischer, A.; Antonietti, M.; Thomas, A. (Angew. Chem., Int. Ed., 2006)

(untitled) - Liu, J.; Zhang, T.; Wang, Z.; Dawson, G.; Chen, W. (J. Mater. Chem., 2011)

(untitled) - Wang, X.; Maeda, K.; Thomas, A.; Takanabe, K.; Xin, G.; Carlsson, J. M.; Domen, K.; Antonietti, M. (Nat. Mater., 2009)

(untitled) - Lotsch, B. V.; Döblinger, M.; Sehnert, J.; Seyfarth, L.; Senker, J.; Oeckler, O.; Schnick, W. (Chem. – Eur. J., 2007)

(untitled) - Bojdys, M. J.; Müller, J.-O.; Antonietti, M.; Thomas, A. (Chem. – Eur. J., 2008)

(untitled) - Jorge, A. B.; Martin, D. J.; Dhanoa, M. T. S.; Rahman, A. S.; Makwana, N.; Tang, J.; Sella, A.; Corà, F.; Firth, S.; Darr, J. A.; McMillan, P. F. (J. Phys. Chem. C, 2013)

(untitled) - Zhang, H.; Yu, A. (J. Phys. Chem. C, 2014)